Ethnobotanical Investigation for Conserving Home Gardens Plants Species in Tambakrejo Sumbermanjing Wetan, Southern of Malang - Pamungkas, Ratih Nila; Hakim, Luchman (Journal of Tropical Life Science, 2013)
In developed countries, traditional knowledge of indigenous people is being widely threatened by current trends of economic globalization especially in destination tourism area such as Tambakrejo village, Sumbermanjing Wetan, Malang. This region includes Sempu Island as well as proposed protected area. Investigation aims were to know diversity of plants species that arranged home garden, used value of each plant species using ethnobotany indexes, and also to describe their methods of preparation and use of the significant plant. The study represents the first step to documenting significant utilitized of the species plant in home garden based on indigenous knowledge before it disappears. Data were collected by depth and semi structured interviews. Informations were about traditional uses of wild plants also cultivated ones. All the collected data were filled in a analytical table and for easier, data was grouped into ten categories, then continued with detailed of use. Data was calculated by using synthetic indexes, those are Relative Frequency of Citation (RFC) and Cultural Importance Index (CI). One hundred and one plants were cited by the informants as being traditionally used in the area. These 100 ethnospecies belonging to 45 families. From 10 categories, most of them concerning allimentary, medical and economic plants. For the allimentary plants, 316 citation, 58 species and 5 different uses were recorded. While for the medical plants, there were 63 citations, 22 species and 4 different uses categories. A few plants species for others categories like erotion control. The study shows that traditional uses for plants especially at home garden still survives as part of the cultural heritage of the community, economic and also for daily activity. Keywords:Ethnobotanical, Home garden, Traditional knowledge